Reliability Estimation of Weibull -Exponential Distribution via Bayesian Approach - Himanshu Pandey; Arun Kumar Rao (Ratio Mathematica, 2021)
Bayesian estimation is employed in order to estimate the reliability function of Weibull-Exponential distribution by using different priors. The Bayes estimators of the reliability function have been obtained under square error, precautionary and entropy loss function